Correlation between vascular endothelial growth factor and quantitative dual-energy spectral CT in non-small-cell lung cancer. Issue 4 (April 2016) - Li, G.J.; Gao, J.; Wang, G.L.; Zhang, C.Q.; Shi, H.; Deng, K.
Abstract : Aim: To explore the correlation between the expression level of vascular endothelial growth factor (VEGF) in non-small-cell lung cancer (NSCLC) tissue and quantitative parameters of spectral computed tomography (CT) imaging. Materials and methods: Forty-eight patients with NSCLC underwent a spectral CT imaging protocol before surgical tumour resection. The repetition of iodine concentration, water concentration, and CT values at 40 keV in the region of interest were measured. The slopes of spectral attenuation curves (λHU ) in the region were also calculated. The level of VEGF expression in the tumour tissue was measured using an immunohistochemical method (MaxVision method). The quantitative parameters of spectral CT imaging were compared among different levels of VEGF expression using one-way analysis of variance (ANOVA) and least significant difference (SLD) test. The correlation between VEGF expression and spectral CT imaging was estimated through Spearman's rank correlation analysis. Results: There were significant differences in iodine concentrations, λHU, and CT values at 40 KeV in NSCLC between the groups showing negative and moderately positive expression of VEGF ( p =0.001, 0.000, and 0.001, respectively) as well as between those showing mildly and moderately positive expression of VEGF ( p =0.047, 0.005, and 0.002, respectively). In addition, all of the iodine concentrations, λHU values, and CT values at 40 KeV displayed a significant and positive correlation with the level of VEGF expression ( r =0.413, 0.458, and 0.393, respectively, p <0.05). Conclusions: Quantitative parameters of spectral CT imaging may be helpful for evaluating the status of angiogenesis in NSCLC. Highlights: The study explored the correlation between the expression level of vascular endothelial growth factor (VEGF) in non-small cell lung cancer (NSCLC) tissue and quantitative parameters of spectral CT imaging. This study highlights a potential role for spectral CT imaging in angiogenesis of NSCLC. To the knowledge of the authors, there are no published data in this area to date.